PERSEPSI GURU PENDIDIKAN DASAR DAN KETERLAKSANAAN PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN MA TEMA TIKA, IP A, DAN IPS - Isti Hidayah; Sugiarto Sugiarto; Margunani Margunani; Arief Widiyatmoko (Jurnal Riptek, 2017)
The l earning whi ch applies s ci entif ic approach emphasizes the process skill. This research aims (1) to find out the teacher’s perception and the implementation of scientific approach; towards the implementation of scientific; (2) to find out and (3) to analyze the implementation of scientific approach in the learning of mathematics, natural sciences, and social sciences at primary school in Semarang in relation to the teacher’s perception towards the implementation of scientific approach in the learning of mathematics, natural sciences, and social sciences at primary school in Semarang. The data of teacher’s perception is gained by using questionnaire, while the data of learning implementation is gained by using observation sheet. The results suggest that the average of teacher’s perception towards the implementation of the 2013 Curriculum is 84.52 (very good), while the average of the implementation of the 2013 Curriculum by the primary school teacher is 72.70 (good). Both of them are significantly different at α = 5%. Reinforcement is needed to strengthen the learning implementation in a form of assistance and motivation such that the implementation of learning can be as good as the teacher’s perception towards learning. The assistance can be done through KKG for elementary school and through MGMP for junior high school.